El sistema de control interno frente al fraude en las empresas del distrito metropolitano de Quito, sector “Clínicas y Hospitales Privados” - Dután Jara, Roselyn Tomasita (2014)
The growth of companies and their business generated today to increase both internal employee activities and their employers, increasing responsibilities and resource management which creates the need to implement a system both effective and efficient internal control generate time savings in the design and analysis of financial statements , so we have focused directly to fraud that could occur within the private clinics and hospitals of the Metropolitan District of Quito DMQ . For the internal control system reliability grant must be in continuous surveillance, so that you can constantly reviewed and updated. Internal control is the responsibility of the Directors of the Company and for this reason should be applied based on measures and policies correctly assigned to each of its opposite case users fall into the commission of fraud , embezzlement and other crimes in the areas most sensitive gaining strength and presenting more complex as it might be in the area of shopping , offices, and consumption.